Nanotechnological immunoassay for rapid label-free analysis of candidate malaria vaccines. Issue 4 (13th January 2021) - Brunetti, Giulio; Padovani, Francesco; De Pastina, Annalisa; Rotella, Chiara; Monahan, Amy; Hoffman, Stephen L.; Jongo, Said A.; Abdulla, Salim; Corradin, Giampietro; Pluschke, Gerd; Daubenberger, Claudia; Hegner, Martin
Abstract : Oscillating micro-cantilever array enables immunoassay for single-step label-free analysis of candidate malaria vaccines. Differential read-out reveals epitope-specific timeline of malaria infection in complex serum samples. Abstract : Malaria is a life-threatening epidemic disease with half of the world's population at risk. Although its incidence rate has fallen since 2010, this ratio dramatically stalled between 2014 and 2018. New fast and optimized tools in vaccine analysis and seroconversion testing are critically needed. We developed a clinical diagnostic device based on piezo-actuated nanoresonators that perform as quantitative in situ calibrated nano-bio sensors for specific detection of multiple target molecules in serum samples. The immunoassay successfully diagnoses humoral immune responses induced by malaria vaccine candidates and reveals the timeline and stage of the infection. We applied the newly developed strategy to a variety of different samples, from pure antibody/vaccine solutions, to blood samples from clinical trials on both naïve and pre-exposed malaria volunteers from sub-Saharan countries. Our nanomechanical assay provides a direct one-step label-free quantitative immunoassay that is on par with the gold-standard, multi-step enzyme-linked immunosorbent assay (ELISA). We achieve a limit of detection of few pg ml −1, or sub-pM concentrations. The 6 μl sample volume allows more than 50 experiments from one finger prick. Furthermore, we simultaneously detected multiple analytes by differential functionalization of multiple sensors in parallel. The inherent differential read-out with in situ controls reduces false positive results. Due to the faster turnaround time, the minimal volume required and the automatized handling system, this technique has great potential for miniaturization and routine diagnostics in pandemic emergencies.